Symposium 5: Variations in the Experience of Phenomenographic Research: Symposium Introduction - Koole, Marguerite; Costello, Jane (Proceedings of the International Conference on Networked Learning, 2012)
Phenomenography originated in the field of Education in the 1970s. At this time, a series of studies were designed to understand why some students appeared to learn more deeply and easily than others (Marton, 1994, Marton & Säljö, 1976). The researchers gathered the different conceptualizations described by the research participants, analyzed their similarities and differences, and noticed that what emerged was a qualitatively limited number of ways of conceptualizing phenomenon. Further, they discovered that these conceptualizations were structurally and referentially related and that these relationships could be mapped hierarchically forming what became known as outcome spaces (Dahlin, 2007). In general, phenomenography aims to find the “variation and the architecture of this variation in terms of different aspects that define the phenomena” (Marton & Booth, 1997, p. 117). Since those early days, phenomenographic methodology has been used in a variety of ways, sometimes combining it with of secondary methods. Hasselgren and Beach list (1997) identify five different types of phenomenography: experimental, discursive (pure), naturalistic, hermeneutic, and phenomenological. The aim of this symposium is to discuss the variation in ways that phenomenography can be applied to research in networked learning. A secondary goal is to open a discussion on the issues and challenges presented by this methodology. The four authors of the papers for this symposium have all taken a discursive (pure) phenomenological approach to their research. What this means is that rather than taking an experimental approach in which learning outcomes were analyzed and measured, as in the experimental approach, the researchers examine conceptions outside of active intervention. That is, the researchers examine how learners conceptualize phenomena occurring in the general learning environment.